0.5-V Nano-Power Shadow Sinusoidal Oscillator Using Bulk-Driven Multiple-Input Operational Transconductance Amplifier - Khateb, Fabian; Kumngern, Montree; Kulej, Tomasz; Yavari, Mohammad (Sensors (Basel, Switzerland), 2023)
This paper presents a low-frequency shadow sinusoidal oscillator using a bulk-driven multiple-input operational transconductance amplifier (MI-OTA) with extremely low-voltage supply and nano-power consumption. The proposed oscillator is composed using two-input single-output biquad filter and amplifiers. The condition and the frequency of oscillation of the shadow oscillator can be controlled electronically and independently using amplifiers. The circuit is designed in Cadence program using 0.18 µm CMOS technology from TSMC. The voltage supply is 0.5 V and the power consumption of the oscillator is 54 nW. The total harmonic distortion (THD) of the output signals is around 0.3% for 202 Hz. The simulation results are in accordance with theory.
Keywords: shadow oscillator; shadow filter; operational transconductance amplifier; analog circuit